Optimalisasi Peran Keluarga dalam Mendampingi Anak Belajar dari Rumah - Ima Ni’mah Chudari; Fatihaturosyidah Fatihaturosyidah (Program Studi PGSD Kampus UPI di Serang, 2020)
Covid-19 pandemic has been affected all sectors of human life, including education. Due to the social-distancing and the Learning from Home (BDR) policy from government, almost all school students now are under the supervision of their parents at home. At a glance, BDR seems like it can provide opportunities for parents to take a bigger role part in their children’s schooling activity. However, BDR has given its side effect on the parents-children behavior and psychological condition. This literature study reveals that BDR gives a very big chance for parents to take more involvements in their children's schooling activities, but on the other hand, BDR is also very potential for children to experience losing opportunities to socialize with their friends and teachers and accepting stress trigger due to the BDR atmosphere which tends to be boring. From these, hopefully parents can do this following breakthrough: (1) be more patient in dealing with children's schooling process and difficulties, (2) vary the learning activity with simple fun games, (3) give breaks between learning activities, (4) establish effective communication between parents and teachers, and last but not the least (5) try to enjoy a new role as a great teacher at home.